Does the intensity in R&D generate start-up's growth? - José L. González-Pernía; Ferran Vendrell-Herrero (European Regional Science Association (ERSA), 2010)
The role of R&D investment on firm's performance is not clear from a theoretical perspective. While the effort in R&D activities conducted internally helps firms to develop the ability to identify, assimilate and apply external knowledge successfully (Cohen and Levinthal, 1990), such activities are costly (Nonaka, Toyama and Nagata, 2000) and take long time to produce new knowledge results (Zahra and Nielsen, 2002). Moreover, the uncertain economic value of new knowledge (Arrow, 1962) may delay the firm's growth. Accordingly, empirical evidence in this regard is mixed (Le, Bruce and Kroll, 2006; Díaz-Díaz; Coad and Rao, 2008; Kotabe, Srinivassan and Aulakh, 2002; Carayannis and Alexander, 2002; Lin, Lee and Hung, 2006). We argue that R&D activities do not have a direct effect on growth since not all new knowledge is economically relevant (Arrow, 1962). To be concise, the indirect relationship between R&D intensity and growth may be mediated by valuable and protected knowledge assets such as patents. We aim to contribute to the literature stream on innovation strategy and new venture growth by analyzing empirically these issues (i.e. direct effect of R&D intensity, and indirect effect of R&D intensity through the mediation of patents, on employment growth of new ventures). In doing so, we build on theoretical notions from the literature on resource-based view (Barney, 1991; Wernerfelt, 1984; Rumelt, 1984) and knowledge production function (Griliches, 1979). Data were collected in a cross sectional setting between February and April of 2008, through a survey addressed to 87 start-ups located in the Basque Country (Spain). According to our results, patents significantly and positively mediate the relation between R&D intensity and new venture growth. In particular, an increment of 1% of R&D intensity indirectly enhances new ventures' employment annual growth in a rate ranging from 0.22% to 0.36%. However, the direct effect of R&D intensity on growth is not significant. This empirical evidence provides entrepreneurs, promoters and policy-makers with an important implication: R&D activities require the mediation role of non-tradable knowledge assets such as patents or other modes of intellectual property in order to appropriate value from knowledge in terms of growth.
Keywords: M13; L25; O14; 330; start-up`s growth; R&D; patent; mediation